Organisational and legal issues of formation of the national ecological network in the Republic of Belarus - Zhloba, Albert A. (Journal of the Belarusian State University. Law, 2024)
The article is devoted to organisational and legal issues of formation (expansion) of the national ecological network in the Republic of Belarus. The author establishes the goals and conditions for the creation of the national ecological network as a complex aggregating object of environmental legal relationship, the procedure for inclusion of protected natural areas into it. Analysing the current legislation, the author defines the problems and suggests ways to solve them.